2012
DOI: 10.9790/3013-0220222224
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of spirometric parameters between active tobacco smokers and tobacco non-smokers

Abstract: Abstract:Aim of this study is to study effect of smoking on various spirometric parameters like forced vital capacity (FVC) , forced expiratory volume in 1 second (FEV 1 ) and FEV 1 / FVC ratio in apparently healthy tobacco smokers and nonsmokers and to compare the result of both the studies to assess the effects of smoking. The present study was carried out by computerized software of Pulmonary Function Test named 'Spiro Excel' on 50 non-smokers and 50 smokers. Smokers are divided in three gropus. Full series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Boskabady et al ,[ 19 ] Karia et al . [ 20 ] and Nawafleh et al . [ 21 ] showed that FEV 1 , FVC, MMEF, PEF were significantly lower in smokers than non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Boskabady et al ,[ 19 ] Karia et al . [ 20 ] and Nawafleh et al . [ 21 ] showed that FEV 1 , FVC, MMEF, PEF were significantly lower in smokers than non-smokers.…”
Section: Discussionmentioning
confidence: 99%